2019
DOI: 10.1016/j.celrep.2019.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Linking YAP to Müller Glia Quiescence Exit in the Degenerative Retina

Abstract: Graphical Abstract Highlights d YAP is required for Xenopus M€ uller glia proliferation in response to injury d YAP is required for mouse M€ uller glia exit from quiescence upon degeneration d YAP5SA reprograms mouse M€ uller glia into highly proliferative cells d YAP functionally interacts with EGFR signaling in M€ uller cells (M.P.) In BriefWhile fish and amphibian M€ uller cells behave as retinal stem cells upon injury, their regenerative potential is limited in mammals. Hamon et al. show that YAP is requir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 75 publications
6
79
0
Order By: Relevance
“…However, it is unclear how chronic MC reactivity in mammals exacerbates injury response leading to glial scar formation. Another important feature of MC reactivity is their exit from quiescence in response to injury [31]. We evaluate MC-cycle reentry using PCNA in both animal models ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear how chronic MC reactivity in mammals exacerbates injury response leading to glial scar formation. Another important feature of MC reactivity is their exit from quiescence in response to injury [31]. We evaluate MC-cycle reentry using PCNA in both animal models ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from our labs, and the lab of Dr Muriel Perron, have identified the Hippo pathway as an essential molecular mechanism that blocks mammalian MG cell cycle entry and reprogramming to a progenitor-like cellular state (Hamon et al, 2019;Rueda et al, 2019). Here, we highlight these data and discuss the advantages of developing additional strategies to unlock the endogenous regenerative potential of the mammalian retina.…”
Section: Introductionmentioning
confidence: 91%
“…For almost two decades, the molecular mechanism suppressing sustained cyclin D3 expression and blocking MG proliferation remained unknown. Recently, we and the lab of Dr Muriel Perron identified signaling by the Hippo pathway as an essential molecular block to sustained MG proliferation and reprogramming to a progenitor-like state (Hamon et al, 2019;Rueda et al, 2019) (Fig. 2).…”
Section: Strategies For Intrinsic Mammalian Retinal Repair: Mg-mediatmentioning
confidence: 99%
See 2 more Smart Citations